2012
DOI: 10.4238/2012.april.27.14
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic and extracellular expression of pharmaceutical-grade mycobacterial 65-kDa heat shock protein in Lactococcus lactis

Abstract: ABSTRACT. Lactic acid bacteria (LAB) are an attractive and safe alternative for the expression of heterologous proteins, as they are nonpathogenic and endotoxin-free organisms. Lactococcus lactis, the LAB model organism, has been extensively employed in the biotechnology field for large-scale production of heterologous proteins, and its use as a "cell factory" has been widely studied. We have been particularly interested in the use of L. lactis for production of heat shock proteins (HSPs), which reportedly pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Azevedo and coworkers showed that L. lactis expressed Hsp65 preparations contained less endotoxin (lypopolysaccharide, LPS) than the limit set by the Food and Drug Administration (FDA) [35]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Azevedo and coworkers showed that L. lactis expressed Hsp65 preparations contained less endotoxin (lypopolysaccharide, LPS) than the limit set by the Food and Drug Administration (FDA) [35]. …”
Section: Resultsmentioning
confidence: 99%
“…As described elsewhere [35], a recombinant L. lactis strain NCDO2118 able to secrete M. leprae Hsp65, using a xylose-inducible expression system (XIES), was constructed. The constructed vector (pSEC: hsp65 ) directed the expression of Hsp65 to the extracellular medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular basis underlying the role of Hsfs in stress tolerance is still not clear. Expression of Hsps as chaperones, including Hsp18.2 and Hsp70, protects cells against injuries associated with various stressors (Simões-Araújo et al, 2003;de Azevedo et al, 2012;Magdalena et al 2012). On the other hand, HsfA1a can bind various promoter targets that are not limited to classical Hsp genes and also include other genes (Guo et al, 2008), implying a broad physiological basis for the stress tolerance role of HsfA1a.…”
Section: A B C Discussionmentioning
confidence: 99%
“…When required, chloramphenicol (10 lg/ml) was added to the media. Hsp65-producer L. lactis (Hsp65 LL; NCDO 2118 strain) which is able to secrete Mycobacterium leprae Hsp65 upon xylose-inducible expression system, was constructed as described elsewhere (de Azevedo et al, 2012). Briefly, a single colony of Hsp65 LL was grown at 30°C, without agitation, in 5 ml of GM17, containing chloramphenicol (10 lg/ml).…”
Section: Lactis Strainsmentioning
confidence: 99%